Development of Merdeka Curriculum Teaching Modules for PjBL-Based Green Chemistry Learning - Said, Umar; Zidny, Robby; Aisyah, Ratna Sari Siti (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2025)
The world of Indonesian education, which is already experiencing a learning crisis, is increasingly affected by the Covid-19 pandemic. The government through the Indonesian Ministry of Education and Culture developed an merdeka curriculum to solve this problem. However, in its implementation, there are still many educators who have not been able to compile teaching modules for the merdeka curriculum. In fact, the learning process of the merdeka curriculum without teaching modules experiences material irregularities. This study aims to develop an “Merdeka Curriculum Teaching Module for PjBL-based Green Chemistry Learning”. The research design used is R&D with the ADDIE model. Literature study and questionnaire data collection techniques. The data analysis technique uses the Aiken's V 0.73 validation instrument on teaching module material and media validated by 10 validators. Teaching modules that were declared valid were tested on 43 student’s of class X SMAN. The results showed that the teaching module was proven valid with a material aspect validity value of 0.96 and a media aspect of 0.95 and obtained student response results with a value of 0.84% (including very good criteria). It can be concluded that the teaching module developed is valid and feasible to use as a school teaching tool.